Parallel Hybrid Powertrain Design for Honda BeAT 110 eSP Scooter to Improve Energy Efficiency and Reduce Emissions - Virgawan Adrian Noes; Muhammad Hamid Ramdhan Nur; Muhammad Nurtanto (Universitas Sultan Ageng Tirtayasa, 2026)
The increasing demand for energy efficiency and emission reduction in urban transportation requires innovative powertrain solutions. This study aims to design and analyze a parallel hybrid powertrain system for the Honda BeAT 110 eSP Scooter. The methodology involves integrating a 3000W BLDC Hub motor on a custom-made 6mm steel bracket arm, coupled with a 60V 27Ah lithium battery, without altering the main frame structure. Performance testing was conducted using a chassis dynamometer and on-road testing to measure fuel consumption, torque, and emissions. The results demonstrate that the hybrid system significantly improves vehicle performance. Fuel efficiency increased to 92 km per charge/refuel combination (compared to 38 km in standard mode). The electric motor produced a peak torque of 81.93 Nm, which is three times higher than the conventional engine's torque of 25.48 Nm. Furthermore, exhaust emissions (CO and HC) were reduced to 0% when operating in electric mode. Despite a 24 kg weight increase, the center of gravity shift remained within safe limits. This research concludes that a modular parallel hybrid system is a viable and efficient solution for urban scooters.